A COMPARATIVE ANALYSIS BETWEEN ENGLISH AND ARABIC PHONEMIC SYSTEM IN "JUST MISSING YOU" SONG LYRICS - Arin Inayah; nur dina (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2021)
This research is a contrastive analysis of phonemic system between English and Arabic in “Just Missing You” song lyrics. The objectives of the research are finding similarities and differences of phonemes in song lyrics to help students learn to pronounce English with Arabic phonemes. This research focus on 24 consonant and 20 vowel phonemes in English and 28 consonant and 6 vowel phonemes in Arabic. The research method is descriptive contrastive with qualitative approach. The method design contrast the phoneme between English and Arabic in song lyrics based on the type of phonemes, they are articulatory phonetic for consonant and height, part of tongue, and shape of lips for vowel. The result of the research found the similarities between English and Arabic phonemic system in “Just missing you” song lyrics which consist of 18 consonant and 6 vowel phonemes. The differences between English and Arabic phonemic system in “Just Missing You” song lyrics consist of 8 consonants and one vowel.